Optimization design and experiment of key components of mountain pendulum-lever cam type hole seeders based on DEM-MBD coupling simulation - Lijun Zhao; Wenke Yin; Bin Yang; Xin Hu; Chuandong Liu; Zihuan Li; Lian Gong; Qiang Li; Bin Li; Shang Li (PLoS ONE, 2025)
In response to issues such as high miss-seeding rates and uneven seed grain distribution during the operation of the pendulum-lever camshaft hole seeders under the compound planting mode of corn and soybeans in hilly mountainous areas, a method for optimizing the hole seeders by adjusting movable pendulum-lever angle and the number of cam roller groups is proposed. By analyzing the motion process and mechanism of hole formation of the hole-forming device, it was possible to elucidate the influence of the movable pendulum-lever angle and cam roller group number on the improvement of seeding quality. Based on the DEM-MBD coupled simulation, single-factor simulation experiments were conducted using the hole seeders shaft speed, movable pendulum- lever angle, and cam roller group number as test factors, with the seed grain qualification rate, reseeding rate, and miss-seeding rate as test indicators. A three-factor, three-level orthogonal rotation combination simulation experiment was designed to derive a mathematical model of the relationship between test factors and indicators. Data analysis was performed using Design-Expert 13 soft-ware to optimize the regression model for multiple objectives and obtain the optimal parameter combination. The simulation test results indicate that when the hole seeder shaft speeds were 47.43 r/min and 48.09 r/min, the movable pendulum- lever angles were 100.23° and 101.70°, and the number of rollers in the cam group were 2.81 and 2.95,the qualified rates of corn and soybean seeding were 95.19% and 96.07%. The reseeding rates were 3.58% and 2.35%, while the missed seeding rates were 1.23% and 1.58%. The field test results indicate that under the optimal parameter combination, the relative errors of the qualification rate, the reseeding rate, and the missed seeding rate between the simulation tests and the field tests were 0.4% and 0.13%, 1.17% and 0.36%, and 1.57% and 0.23%. This serves to validate the accuracy of the coupled simulation model, and the research findings can provide theoretical support and a point of reference for the design and performance optimization of pendulum- lever cam-type hole seeders in hilly and mountainous areas.